2012
DOI: 10.5754/hge11458
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection with Sheath-Assisted Counter Traction Using a Novel Sheath for Early Gastric Cancers

Abstract: Sheath-assisted counter traction ESD by the novel sheath was technically simpler and thus less time-consuming regardless of the location of lesions, especially when =20mm in diameter. The traction ESD with the novel sheath is safe and not invasive, and it can be universally applied to standard ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…We identified 4 studies 18,20,21,23 evaluating various methods to improve traction during an ESD procedure. More than a decade ago, Yonezawa et al, 18 in a well-designed, 12-month follow-up prospective trial of 60 patients, showed that the use of a sophisticated double-channel endoscope ("R-scope") resulted in significantly shorter operating time than standard ESD (57.9±29.7 min vs. 92.8±58.9 min, p=0.016), with similar efficacy and complication rates.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 4 studies 18,20,21,23 evaluating various methods to improve traction during an ESD procedure. More than a decade ago, Yonezawa et al, 18 in a well-designed, 12-month follow-up prospective trial of 60 patients, showed that the use of a sophisticated double-channel endoscope ("R-scope") resulted in significantly shorter operating time than standard ESD (57.9±29.7 min vs. 92.8±58.9 min, p=0.016), with similar efficacy and complication rates.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…All but 2 studies 38,46 were conducted in a single-site setting. Twenty-three had a prospective design [18][19][20][21][22][23]26,27,29,30,32,33,35,[37][38][39][40][41][44][45][46][47]50 and 10 had a retrospective design. 24,25,28,31,34,36,42,43,48,49 Among the prospective studies, 6 were randomized controlled trials (RCTs).…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 13 eligible articles of gastric ESD, we identified two RCTs, and 11 retrospective comparative studies. [22][23][24][25][26][27][28][29][30][31][32][33][34] Ten studies compared the efficacy of ESD traction devices, and three other studies investigated the efficacy of traction strategy compared with conventional ESD ( Table 2).…”
Section: Stomachmentioning
confidence: 99%
“…Other traction devices such as sheath, elastic band, and S-O clip-assisted ESD were also shown to be effective in reducing the procedural time compared with conventional ESD in some retrospective studies. 25,27,28 In addition, submucosal tunneling technique and water-pocket creation strategy were recently reported to provide efficient traction. 23,24,34 Among them, Zhang et al 34 only included gastric epithelial neoplasms located in the lesser curvature.…”
Section: Stomachmentioning
confidence: 99%